An immunochromatographic test using whole blood for rapid diagnosis of human paragonimiasis and its diagnostic usefulness - Patcharaporn Boonroumkaew; Lakkhana Sadaow; Penchom Janwan; Rutchanee Rodpai; Oranuch Sanpool; Tongjit Thanchomnang; Hiroshi Yamasaki; Pewpan M. Intapan; Wanchai Maleewong (Food and Waterborne Parasitology)
Paragonimiasis is a harmful food-borne zoonosis caused by lung flukes of the genus Paragonimus. The disease is found on most continents, several million people are at risk of infection, and it is a re-emerging disease in developing countries. The gold standard for diagnosis of pulmonary paragonimiasis requires the finding of eggs in sputa and/or fecal samples. In ectopic paragonimiasis cases, eggs are typically not seen, and supportive information is required such as a history of eating freshwater crabs or crayfishes, radiographic findings and immunological tests. Here, we developed a proof of concept based on lateral flow assay, an immunochromatographic test kit, named the paragonimiasis whole-blood test kit, for detection of specific IgG antibody in simulated whole-blood samples (WBSs) using worm excretory-secretory antigens to diagnose human paragonimiasis. The laboratory diagnostic values of this kit were compared with the detected IgG in serum samples. In simulated WBSs, the diagnostic sensitivity and specificity were 97.8 % and 96.1 %, respectively, while for serum samples, these values were 100.0 % and 94.8 %, respectively. The comparative IgG antibody detections whether a result was positive or negative between simulated WBSs and serum samples did not differ significantly with a concordance of 97.8 % in laboratory conditions using a circumscribed set of samples. The tool is fast and easy to use. The next step involves observing and evaluating native whole blood samples and using specific recombinant antigens need to be evaluated for support diagnosis of paragonimiasis caused by P. heterotremus, P. westermani and P. miyazakii at the bedside or at local and remote hospitals with limited facilities. It will also be valuable for epidemiological surveys in Asia where paragonimiasis is endemic.